2020
DOI: 10.1103/physrevx.10.041006
|View full text |Cite
|
Sign up to set email alerts
|

Broken Symmetries and Kohn’s Theorem in Graphene Cyclotron Resonance

Abstract: The cyclotron resonance of monolayer graphene, encapsulated in hexagonal boron nitride and with a graphite backgate, is explored via infrared transmission magnetospectroscopy as a function of the filling factor at fixed magnetic fields. The impact of many-particle interactions in the regime of broken spin and valley symmetries is observed spectroscopically. As the occupancy of the zeroth Landau level is increased from half-filling, a nonmonotonic progression of multiple cyclotron resonance peaks is seen for se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…This plot reproduces the observed eyeglass-like pattern for −2 < ν < 2 and also explains the weaker intensities of the signals at higher magnetic fields (e2 and h2) with respect to those of the signals at lower magnetic fields (e1 and h1). Our CR experiment suggests that Δ g spin ∼ 12 when E F lies in the middle of the spin gaps (|ν| = 1), which is consistent with the observations from a recent STM study and CR spectrocopy. , We note that although we assumed B CR versus ν is constant for |ν| > 2 (Figure f), the experiment reveals arc-like shapes for the CR signals when |ν| > 2 (Figure e). This observation suggests that v F renormalization occurs, depending on ν, because of the different degrees of many-particle interactions (see the Supporting Information).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…This plot reproduces the observed eyeglass-like pattern for −2 < ν < 2 and also explains the weaker intensities of the signals at higher magnetic fields (e2 and h2) with respect to those of the signals at lower magnetic fields (e1 and h1). Our CR experiment suggests that Δ g spin ∼ 12 when E F lies in the middle of the spin gaps (|ν| = 1), which is consistent with the observations from a recent STM study and CR spectrocopy. , We note that although we assumed B CR versus ν is constant for |ν| > 2 (Figure f), the experiment reveals arc-like shapes for the CR signals when |ν| > 2 (Figure e). This observation suggests that v F renormalization occurs, depending on ν, because of the different degrees of many-particle interactions (see the Supporting Information).…”
supporting
confidence: 90%
“…Figure 4f 1), which is consistent with the observations from a recent STM study 39 and CR spectrocopy. 41,42 We note that although we assumed B CR versus ν is constant for |ν| > 2 (Figure 4f), the experiment reveals arc-like shapes for the CR signals when |ν| > 2 (Figure 4e). This observation suggests that v F renormalization occurs, depending on ν, because of the different degrees of many-particle interactions (see the Supporting Information).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The magneto-optical response of systems with such a LL spectrum has been widely studied, both theoretically and experimentally, on graphene and other systems [46,47,[49][50][51][52][53][54][55]. The response is dominated by a series of interband and intraband inter-LL excitations that follow the standard electric-dipole selection rules in isotropic systems: n → n ± 1.…”
Section: Magneto-optical Response Of Surface Statesmentioning
confidence: 99%
“…Recently, Russell et al [35] have reported a direct signal of manybody effects on CR in high-mobility hBN-encapsulated monolayer graphene; see also ref. [36]. They observed significant variations of resonance energies over a finite range of filling factor ν under a fixed magnetic field B; the point lies in extracting genuine Coulombic effects as a function of ν while controlling the running of the velocity factor with B.…”
Section: Introductionmentioning
confidence: 98%